Managing the Myth of Ecotourism: A Queensland Case Study - Peace, Adrian (The Australian journal of anthropology, 2005)
Although social anthropologists are taking an increased interest in tourism in Australia, not much attention has been paid thus far to the sites from which visitors take off into the bush, wilderness or nature. Tourist resorts and lodges are not simply the locations in which basic needs are met before more energetic activities begin. Especially in ecotourist settings, important ideological claims are made about their built environments as well as the everyday practices and localised activities which are ongoing in these discursive sites. This paper provides an ethnographic analysis of one such ecotourist resort. It aims to detail the myths which are manufactured about its relation to the island environment in which it is situated, and to the world beyond.